AN ASSESSMENT OF CLINICAL EFFICACY OF HYPOTHERMIC THERAPY FOLLOWING MILD TRAUMATIC BRAIN INJURY IN THE ADOLESCENT ATHLETE AS COMPARED TO AN UNTREATED ACTIVE CONTROL POPULATION. Issue 4 (28th April 2020) - Congeni, Joseph; Murray, Tamara; Zak, John; McNinch, Neil L.; Kline, Peyton; Morgan, Danielle
Background: Hypothermic therapy has been shown to have clinical efficacy in a variety of cardiovascular injuries including cardiac arrest and myocardial infarction. 1 It is standard of care for the treatment of neonates with hypoxic-ischemic encephalopathy (HIE) and has shown improved outcomes with traumatic brain injury (TBI) 2, and sports-related injuries. Additionally, in several anecdotal studies, cold therapy has been hypothesized to be equally as effective in limiting the damaging effects of the body's response to mild traumatic brain injury, commonly known as concussion; but the primary limitation of these studies has been sample size. 3, 4 Hypothesis/Purpose: This study is being conducted to quantify the clinical safety and efficacy of head and neck cooling when applied after mild traumatic brain injury (mTBI) among adolescents participating in sporting activities. Methods: A multi-center, prospective, randomized, non-blinded, dual-arm comparator study employing an adaptive design with two-phases: the 60-patient pilot study presented here, and the pivotal phase currently underway. After randomization, subjects in the standard of care arm receive brain rest. Subjects in the treatment group receive brain rest plus 30 minutes of cooling therapy at the initial and 72 hour visits. Primary endpoint: SCAT5 symptom severity score, evaluated from initial clinic visit through 4 weeks post injury. SCAT5 measured at initial visit (pre/post treatment, both arms), 72 hour visit (pre/post treatment for intervention arm, once for standard of care arm) and once at 10 day and 4 week follow up visits for both arms. Results: To evaluate primary endpoint, a Repeated Measures Analysis of Variance was conducted as intended for pivotal phase, with unstructured covariance and utilizing last observation carried forward technique. Dependent variable modelled as absolute change from initial SCAT5. Significant main effects and interaction effects noted (p-value < 0.01, < 0.01 and 0.02 respectively). To evaluate secondary endpoint, a Wilcoxon Rank Sum Test was conducted to examine potential differences in ImPACT Cognitive Efficiency Index, there was no evidence in the sample of significant differences (p-value = 0.600). All testing evaluated at alpha level of significance = 0.05. Conclusion: Preliminary results from pilot phase indicate significant treatment effects that change differently over time, depending on group. Pivotal phase to determine efficacy is currently underway. Tables/Figures: Table 1.1. Summary Statistics for Baseline Demographics and Clinical Outcomes; Repeated Measures ANOVA Results Summary Statistics Standard of Care Arm (n = 27) Treatment Arm (n = 28) Mean (SD) Min/Max Mean (SD) Min/Max Age at Consent (yrs) 14.3 (1.4) 12.0/17.0 14.7 (1.6) 12.0/17.0 Height 167.9 (9.6) 141.0/184.9 169.1 (9.2) 151.5/188.0 Weight 66.9 (16.6) 40.1/105.0 66.1 (17.6) 36.7/116.2 SCAT5 Absolute Differences Baseline - Time 1 (Initial Visit, Post Tx Score) 0.9 (14.2) -40.0/33.0 -13.2 (13.0) -48.0/7.0 Baseline - Time 2 (72 Hr Visit, Pre Tx Score) -2.6 (9.6) -21.0/19.0 -11.8 (12.1) -40.0/7.0 Baseline - Time 3 (72 Hr Visit, Post Tx Score) -3.7 (12.7) -40.0/19.0 -19.2 (14.0) -54.0/0.0 Baseline - Time 4 (10 Day Visit) -13.9 (14.9) -45.0/15.0 -19.8 (13.6) -55.0/4.0 Baseline - Time 5 (4 Wk Visit) -22.7 (20.3) -63.0/12.0 -23.4 (17.3) -76.0/4.0 Repeated Measures ANOVA Post Hoc Pairwise Analyses: SCAT5 Mean Difference Between Groups (95% Confidence Interval) Baseline - Time 1 (Initial Visit, Post Tx Score) 14.1 (6.7, 21.4) Baseline - Time 2 (72 Hr Visit, Pre Tx Score) 9.2 (3.3, 15.1) Baseline - Time 3 (72 Hr Visit, Post Tx Score) 15.5 (8.2, 22.8) Baseline - Time 4 (10 Day Visit) 5.8 (-1.9, 13.5) Baseline - Time 5 (4 Wk Visit) 0.7 (-9.5, 10.9) Figure 1.2. References: The effect of mild induced hypothermia on outcomes of patients after cardiac arrest: a systematic review and meta-analysis of randomized controlled trials. Zhang et al . Critical Care (2015) 19:417. Therapeutic hypothermia for acute brain injuries. Andresen et al . Scandinavian Journal of trauma, Resuscitation and Emergency Medicine (2015) 23:42. The effect of selective head-neck cooling on physiological and cognitive functions in healthy volunteers. Jackson et al . Translational Neuroscience (2015) 6:131. Neurobiological effect of selective brain cooling after concussive injury. Walter et al. Brain imaging and behavior (2018) 2:891.